Informed Rejection: A Theoretical Framework for Transparent Recruitment and Structured Feedback - Kumar, Abhishek; Avidra, Saurabh (Journal of Neonatal Surgery, 2025)
The study addresses key challenges in India's recruitment landscape. These include vague job advertisements. The absence of structured feedback is also a problem. 73% of applicants do not receive any response, which is called ghosting. These issues undermine fairness and trust. This is particularly seen in the private and academic sectors. A transparent recruitment model is proposed to address this. The model is based on systems theory, equity theory and social exchange theory. It lays down clear evaluation criteria. The criteria include weightings, such as academics -40%, technical skills -35%, communication -25%. It also lays down sub-categorization and rejection thresholds. Testing methods for each component are also included. The model ensures that every applicant receives a response within a week. The feedback will be specific and actionable. It is tailored to the cultural context of India. The model was operationalized using the Design Science Research (DSR) methodology and validated through sample job advertisements across sectors like IT, engineering, finance, marketing, and academia. Comparative analysis shows the model's superiority over current Indian practices, which lack clarity, testing specificity, and feedback. The propose framework significantly enhances candidate experience, transparency, and trust. Furthermore, realworld rejection scenarios illustrate how the model provides either threshold-based or performance based feedback, encouraging candidates' future development with tailored suggestions and learning resources. Overall, the study offers a scalable, equitable, and culturally sensitive recruitment solution, aimed at professionalizing hiring processes in India and reducing ambiguity and disengagement in job applications..